Cost Per Participant Recruited From Rural and Remote Areas Into a Smoking Cessation Trial Via Online or Traditional Strategies: Observational Study - Byaruhanga, Judith (J Med Internet Res, 2019)
BACKGROUND: Rural and remote residents are more likely to smoke than those who live in major cities; however, recruitment of research participants from rural and remote areas can be challenging. The cost per participant recruited from rural and remote areas via online (eg, social media) and traditional strategies (eg, print) has implications for researchers on how to allocate resources to maximize the number of participants recruited. Participant characteristics such as demographics, financial stress, mental health, and smoking-related factors may be associated with recruitment method (ie, online vs traditional), and so it is important to understand whether certain subgroups are more likely to be recruited via a particular strategy. OBJECTIVE: This study aimed to determine the cost per participant recruited and examine whether characteristics such as demographics, financial stress, mental health, and smoking-related factors may be associated with the recruitment method (ie, online vs traditional). METHODS: Participants were recruited into a randomized trial that provided smoking cessation support. Eligible participants were aged 18 years or older; used tobacco daily; had access to video communication software, internet, and telephone; had an email address; and lived in a rural or remote area of New South Wales, Australia. This study describes the natural (observed) experience of recruiting participants via online and traditional methods into a smoking cessation trial. RESULTS: Over 17 months, 655 participants were recruited into the smoking cessation trial. A total of 88.7% (581/655) of the participants were recruited via online methods. Moreover, 1.8% (12/655) of the participants were recruited from remote locations and none from very remote areas. The cost per participant recruited by the various online strategies ranged from Aus $7.29 (US $4.96, £4.09, and €4.43) for Gumtree, a local online classified website, to Aus $128.67 (US $87.63, £72.20, and €78.28) for email. The cost per participant recruited using traditional strategies ranged from Aus $0 (US $0, £0, and €0) for word of mouth to Aus $3990.84 (US $2757.67, £2227.85, and €2477.11) for telephone. Women had greater odds of being recruited via online methods than men (odds ratio 2.50, 95% CI 1.42-4.40). No other characteristics were associated with the recruitment method. CONCLUSIONS: The cost per participant recruited via online and traditional strategies varied, with the range being smaller for online than traditional recruitment strategies. Women have greater odds of being recruited via online strategies into rural smoking cessation trials. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12617000514303; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372584&isReview=true